2015
DOI: 10.1017/s0022377815001385
|View full text |Cite
|
Sign up to set email alerts
|

Self-phase modulation in various regimes of intense laser–plasma interactions

Abstract: Creation of plasmas by intense laser pulses and consequent laser–plasma interactions involve highly non-linear processes. In particular, a variation of the refractive index induced by the laser action turns into a self-phase modulation (SPM) of the laser field. This effect, already observed with nanosecond laser pulses, achieves striking evidence with ultra-short pulses whose intensity can produce index changes in a time as short as a single optical cycle. In this condition, spectral modifications of the laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…This demonstrates the existence of a parameters region where the laser intensity reaches a maximum value independent from the energy ratio between the prepulse and the main pulse. Previous works demonstrated that blue-shifts of some tens of nanometers can be related to efficient multi-photon ionization, and a constant shift can be related to a fixed laser intensity (Giulietti & Giulietti, 2015 and references therein; Koga et al, 2000). This leads to the conclusion that the role of the prepulse is in modifying the index of refraction of the air plasma, determining a maximum intensity for the main pulse capable to interact with the air-Sn plasma accelerating electrons up to many keV.…”
Section: Correlation Between X-ray and Near-infrared Spectramentioning
confidence: 98%
“…This demonstrates the existence of a parameters region where the laser intensity reaches a maximum value independent from the energy ratio between the prepulse and the main pulse. Previous works demonstrated that blue-shifts of some tens of nanometers can be related to efficient multi-photon ionization, and a constant shift can be related to a fixed laser intensity (Giulietti & Giulietti, 2015 and references therein; Koga et al, 2000). This leads to the conclusion that the role of the prepulse is in modifying the index of refraction of the air plasma, determining a maximum intensity for the main pulse capable to interact with the air-Sn plasma accelerating electrons up to many keV.…”
Section: Correlation Between X-ray and Near-infrared Spectramentioning
confidence: 98%
“…As described in the next section, the local variation of n e on a timescale comparable with the laser wave period T 0 = 2π/ω 0 induces a consequent spectral change of the laser light. Usually such fast µ-variations are directly or indirectly produced by the action of the intense laser light on the medium and the process is then called Self-Phase Modulation (SPM) [1]. Beside laser-plasma interaction, SPM has been studied theoretically and experimentally in a variety of contexts and in some cases it has been used for important applications.…”
Section: Introductionmentioning
confidence: 99%